Doença pulmonar obstrutiva crônica - Pelegrino, Nilva Regina Gelamo; Godoy, Irma de [UNESP] (My University, 2001)
In this review the definition of COPD is presented and the epidemiology and risk factors for disease development are briefly discussed. Characteristics clinical features, pulmonary functions indices, radiologics signs and arterial blood gases alterations are presented and discussed. Classification of disease severity and components of COPD management are also described.
Chronic obstrutive pulmonary disease
Keywords: Chronic obstrutive pulmonary disease; Diagnosis; Treatment; aminophylline; beta 2 adrenergic receptor stimulating agent; bronchodilating agent; cholinergic receptor blocking agent; fenoterol; formoterol; ipratropium bromide; methylxanthine derivative; salbutamol; salmeterol; terbutaline; theophylline; chronic obstructive lung disease; clinical feature; disease severity; human; hypercapnia; hypoxemia; pulmonary hypertension; radiodiagnosis; review; risk factor; stomach pH; treatment outcome